Glimpse of avian diversity near Mithiviradi Village, Bhavnagar District, Gujarat, India - Vaghela, Viral M.; Dodia, Pravinsang P (International Multidisciplinary Research Journal, 2020)
Birds are very good biological indicators of environment health. Changes in various activity of bird can be used to check the long term effects of changes in habitat. The study was conducted to find out the diversity of birds in and around Mithiviradi village (21o3006 N; 72o1349E) located in Talaja tehsil, Bhavnagar, Gujarat. The avian diversity was surveyed during Jan. 2016 to Jan. 2018. During the survey total 104 bird species were recorded out of this 78 species were residential and breeding, 15 species were migratory, and 09 were resident, breeding and migratory. This avian diversity represents 16 orders and 50 families.